Identifikasi Faktor – Faktor Yang Memengaruhi Keberhasilan Usaha Kopi Jantan Toraja (Studi Kasus Pada UMKM Kopi 1000 Nurhidayah) - Dwi Prasetyawati Thana; Gidion Aryo Nugraha Pongdatu; Agustinus Mantong; Hariadi Hariadi (Forum Agribisnis, 2021)
A source of income for farmers would be 'Kopi Jantan Toraja' (Peaberry coffee). The growing demand due to changes in the lifestyles of people makes today's coffee more popular. 'Kopi Jantan Toraja' is one of the interesting business options to be produced to boost the farmers' economy. This study aims to define and evaluate the internal and external factors of the "Kopi Jantan Toraja" company in the hope that the internal conditions examined can enable farmers to explore the strengths and weaknesses as well as the opportunities or challenges and threats to be addressed in the company. Internal and external environmental analysis is the type of data collection and analysis used in this study. IFE and EFE in the early phases (Internal and External Factor Evaluation). In the next step, the status of the "Kopi Jantan Toraja" company was calculated by the IE Matrix analysis method. 19 (nineteen) internal factors (8 strengths and 11 weaknesses) and 14 (fourteen) external factors were seen in the IFE and EFE study (8 opportunities and 6 threats). Based on the IE matrix, UMKM Kopi 1000 Nurhidayah's "Kopi Jantan Toraja" company is in a position to keep and sustain, suggesting that a viable approach used by UMKM Kopi 1000 Nurhidayah is market penetration and product growth strategy.